IPAtranscriptor: A Python program for narrow phonetic transcription for blind and sighted linguists - Braun, Almut (Journal of the International Phonetic Association, 2020)
IPAtranscriptor is a tool for creating narrow phonetic transcriptions. As it connects to the computer's default text-to-speech engine on demand, the program can be used not only by sighted but also by partially sighted and blind individuals. Sighted users can choose whether they prefer the mouse or the keyboard as their input device. In contrast to other programs, the full set of symbols and diacritics of the International Phonetic Alphabet (IPA) is implemented and users can produce very narrow phonetic transcriptions as they can insert up to three diacritics above and three diacritics below each IPA symbol to modify it. Furthermore, the program can facilitate the collaboration between blind and sighted phoneticians (or students of linguistics in general) since they can easily exchange their phonetic transcriptions. A conversion of the transcriptions is not necessary as all transcribers can use the same system regardless of their visual abilities. IPAtranscriptor is freely available online and is believed to be the first audio-based program for narrow phonetic transcription that can be used by blind and sighted phoneticians.